The effects of maternal and paternal exposure to tramadol on rat prenatal foetuses - R.M, El-Balshy; M.E, Zowail; E. H, Nafie; S.H, Abou-Bakr (International Journal of Biological Research, 2021)
The presented study was conducted to investigate the effects of different doses of tramadol on the prenatal foetuses of rat at 20th day of gestation. The animals were divided into five groups; Control group (C), received saline orally; G1administered with (1/6 LD50; 50 mg/kg); G2 was given (1/10 of LD50; 30 mg/kg) and G3& G4 were treated with low doses of tramadol (1/50 of LD50; 6 mg/kg) and (1/100 of LD50; 3 mg/kg) respectively. Males and females were administered with tramadol for 7 days before mating, then they mate with each other and pregnant females continued treatment with tramadol to the 20th day of gestation. Tramadol significantly decreased body weight and length of foetuses and increased percentage of dead foetuses. Besides the early death of foetuscs which become resorbed during the gestation period, few foetuses died at the end of gestation period and remain as stillbirth. The percentage of mortality of resorbed foetuses and sillbirth is generally increased in the treated groups. Tramadol treatment caused retarded ossification of some bones and shortness of others. Numerous histopathological changes were detected in liver, kidneys, and lungs of the parentally treated foetuses rat tissues.Â Â